A prospective study of long term prognosis in young myocardial infarction survivors: the prognostic value of angiography and exercise testing. Issue 8 (14th July 2003) - Awad-Elkarim, A A; Bagger, J P; Albers, C J; Skinner, J S; Adams, P C; Hall, R J C
Abstract : Objectives: To define the ability of early exercise testing and coronary angiography to predict prognosis in young survivors of myocardial infarction (MI). Methods: 255 consecutive patients (210 men) aged 55 years or less (mean 48 years) admitted to hospital (1981–85) were eligible. Of these, 150 patients (130 men) who were able to exercise early after MI and underwent coronary angiography within six months constituted the study group and were followed up for up to 15 years. Survival data up to 18 years was obtained for the whole cohort. Results: Survival at a median of 16 years was 52% for the whole cohort, 62% for the study group, and 48% for the excluded group. From nine years onwards survival deteriorated significantly in the study group compared with an age matched background population. Fifteen years after MI, 121 patients (81%) in the study group had had at least one event (death, MI, revascularisation, cardiac readmission, stroke) leaving 29 (19%) event-free. The number of diseased vessels was the major determinant of time to first event (p = 0.001) and event-free survival (p = 0.04). Exercise duration was also important in the prediction of time to first event (p = 0.003). Death was influenced by a history of prior MI. Conclusion: The favourable initial survival was followed by significant deterioration after nine years. This late attrition is an important treatment target. Furthermore, this study supports risk stratification early after MI combining angiography with non-invasive tools.